Modeling end-user adoption of e-government services in Abu Dhabi - Kabbar, Eltahir Fadul (Curtin University, 2016)
A number of recent reports indicate that many governments around the world are increasingly using internet technologies to provide public services. However little is known about the factors that influence end-users’ adoption of these services, particularly in a non-western context. This study used mixed research methods to build, empirically test and validate an e-government adoption model. The findings will be useful to both e-government researchers and practitioners interested in promoting e-government.